2014
DOI: 10.1161/atvbaha.113.302878
|View full text |Cite
|
Sign up to set email alerts
|

Deficiency of Endothelial Cxcr4 Reduces Reendothelialization and Enhances Neointimal Hyperplasia After Vascular Injury in Atherosclerosis-Prone Mice

Abstract: Objective— The Cxcl12/Cxcr4 chemokine ligand/receptor axis mediates the mobilization of smooth muscle cell progenitors, driving injury-induced neointimal hyperplasia. This study aimed to investigate the role of endothelial Cxcr4 in neointima formation. Approach and Results— β-Galactosidase staining using bone marrow x kinase ( Bmx ) -CreER T2 … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
62
0

Year Published

2014
2014
2019
2019

Publication Types

Select...
9
1

Relationship

2
8

Authors

Journals

citations
Cited by 59 publications
(65 citation statements)
references
References 60 publications
3
62
0
Order By: Relevance
“…In our experiments, Bmx silencing completely abrogated STAT3 activation by Ang II in endothelial cells and also significantly attenuated phosphorylation in vivo. Although we cannot fully exclude the possibility that Bmx functions also in cardiomyocytes, our results and those of others strongly suggest that Bmx mainly acts in endothelial cells (24). Thus, the present results highlight the importance of endothelial cell-to-cardiomyocyte signaling in cardiac remodeling (see the schematic summary in Fig.…”
Section: Discussionsupporting
confidence: 59%
“…In our experiments, Bmx silencing completely abrogated STAT3 activation by Ang II in endothelial cells and also significantly attenuated phosphorylation in vivo. Although we cannot fully exclude the possibility that Bmx functions also in cardiomyocytes, our results and those of others strongly suggest that Bmx mainly acts in endothelial cells (24). Thus, the present results highlight the importance of endothelial cell-to-cardiomyocyte signaling in cardiac remodeling (see the schematic summary in Fig.…”
Section: Discussionsupporting
confidence: 59%
“…CXCR4 is classified as a Gi-coupled G protein-coupled receptor and is expressed on the surface of endothelial cells (ECs). 2 Although there are several reports showing that SDF-1α/CXCR4 signal activation promotes EC migration, proliferation, and nitric oxide (NO) production, [3][4][5] additional roles for SDF-1α on ECs remain unknown.…”
mentioning
confidence: 99%
“…However, the cell type-specific effects remained to be addressed. Noels et al 28 investigated the specific effects of endothelial CXCR4 on injury-induced neointima formation. This study showed that endothelial CXCR4 deficiency significantly increased neointima formation and that formed lesions in these mice contained a higher number of macrophages, but reduced number of SMCs and collagen content.…”
Section: Vessel Injurymentioning
confidence: 99%